Dual aggregation-induced emission for enhanced fluorescence sensing of furin activity in vitro and in living cells - Liu, Xiaomei; Liang, Gaolin (Chemical communications (Cambridge, England), 2017)
The aggregation-induced emission (AIE) effect has recently been widely applied for biomarker sensing. But developing “smart” strategies to effectively aggregate the AIE fluorogen and additionally enhance the fluorescence emission remain challenging. In this work, by integrating a biocompatible condensation reaction with an AIE fluorogen, we rationally designed a “smart” dual AIE probe Ac-Arg-Val-Arg-Arg-Cys(StBu)-Lys(TPE)-CBT ( 1 ) for enhanced fluorescence sensing furin activity in vitro and in living cells. Compared with the single AIE probe Ac-Arg-Val-Arg-Arg-Lys(TPE)-OH ( 1-Ctrl ) which also subjects to furin cleavage, fluorescence emissions of 1 were additionally enhanced 1.7 fold and 3.4 fold in vitro and in living cells, respectively. We envision that, in the near future, our “smart” strategy of enzyme-instructed dual AIE could be widely applied for sensing (or imaging) enzyme activity in vitro and even in vivo with dramatically enhanced sensitivity.